Impact of Prior Unilateral Chest Wall Radiotherapy on Outcomes in Bilateral Breast Reconstruction. Issue 4 (October 2016) - de Araujo, Thiago B.; Jue Xu, Mary; Susarla, Srinivas M.; Shmelev, Karen; Jiang, Wei; Pribaz, Julian J.; Hergrueter, Charles; Carty, Matthew J.; Caterson, Stephanie; Chun, Yoon S.
Abstract : Background: The purpose of this study was to evaluate the impact of prior unilateral chest wall radiotherapy on reconstructive outcomes among patients undergoing bilateral immediate breast reconstruction. Methods: A retrospective evaluation of patients with a history of unilateral chest wall radiotherapy was performed. In each patient, the previously irradiated and reconstructed breast was compared to the contralateral nonirradiated side, which served as an internal control. Descriptive and bivariate statistics were computed. Multiple regression statistics were computed to identify adjusted associations between chest wall radiotherapy and complications. Results: Seventy patients were included in the study. The mean follow-up period was 51.8 months (range, 10 to 113 months). Thirty-eight patients underwent implant-based breast reconstruction; 32 patients underwent abdominal autologous flap reconstruction. Previously irradiated breast had a significantly higher rate of overall complications (51 percent versus 27 percent; p < 0.0001), infection (13 percent versus 6 percent; p = 0.026), and major skin necrosis (9 percent versus 3 percent; p = 0.046). After adjusting for age, body mass index, reconstruction method, and medical comorbidities, prior chest wall radiotherapy was a significant risk factor for breast-related complications (OR, 2.98; p < 0.0001), infection (OR, 2.59; p = 0.027), and major skin necrosis (OR, 3.47; p = 0.0266). There were no differences between implant-based and autologous reconstructions with regard to complications ( p = 0.76). Conclusion: Prior chest wall radiotherapy is associated with a 3-fold increased risk of postoperative complications following immediate breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.